2019
DOI: 10.1159/000495301
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Procedural Pain in Critically Ill Patients by Music Therapy: A Randomized Controlled Trial

Abstract: Background: This study aimed to determine the effectiveness of music listening for procedural pain relief using two different observational pain tools during endotracheal suctioning. Materials and Methods: This study was a randomized controlled trial. The sample of the study included 98 patients with mechanical ventilation support who met the selection criteria. The patients were randomly assigned to control and music therapy groups. Patients in the control group were routinely suctioned as usual. Patients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…These results extend the efficacy of previous studies utilizing music therapy and a catheter size of 12 in reducing pain intensity and agitation. 2,5,11,25,27,28 This study also supports the efficacy of the application of 3-phase procedural pain management in relieving the painful procedures employed in previous studies. 3,8,10,[17][18][19]29 These results illustrate the benefit of using a systematic EBP process and translating the current best available evidence into nursing practice to provide high-quality care and positive outcomes for patients.…”
Section: Discussionsupporting
confidence: 81%
“…These results extend the efficacy of previous studies utilizing music therapy and a catheter size of 12 in reducing pain intensity and agitation. 2,5,11,25,27,28 This study also supports the efficacy of the application of 3-phase procedural pain management in relieving the painful procedures employed in previous studies. 3,8,10,[17][18][19]29 These results illustrate the benefit of using a systematic EBP process and translating the current best available evidence into nursing practice to provide high-quality care and positive outcomes for patients.…”
Section: Discussionsupporting
confidence: 81%
“…Based on the search and the feasibility test, 19 RCTs were related to music therapy in critical care units (Table 4) [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The various types of music used in this study were classical music and instrumental music produced from various musical instruments (piano, harp, guitar, flute, and others), natural sound-based music, religious music to traditional music in their respective countries.…”
Section: Interventions Of Music Therapymentioning
confidence: 99%
“…From a review of various studies, it shows that in principle, music that can be used as therapy was music with a relaxing rhythm, soft tones, and slow rhythms. Nine (9/19) RCT states that music tempo ranges from 60 to 80 beats/min [14], [15], [16], [17], [20], [21], [22], [24], [25]. Each study used a different volume, starting from 30 to 40 dB [20], 50-60 dB [18], or determined by a nurse [31], and others reported that the music volume was adjusted to the participant's preference or set at an adequate level for each participant.…”
Section: Interventions Of Music Therapymentioning
confidence: 99%
See 2 more Smart Citations